Presynaptic α4β2 nicotinic acetylcholine receptors increase glutamate release and serotonin neuron excitability in the dorsal raphe nucleus - Garduño, Julieta; Galindo-Charles, Luis; Jiménez-Rodríguez, Javier; Galarraga, Elvira; Tapia, Dagoberto; Mihailescu, Stefan; Hernandez-Lopez, Salvador (The Journal of neuroscience, 2012)
Several behavioral effects of nicotine are mediated by changes in serotonin (5-HT) release in brain areas that receive serotonergic afferents from the dorsal raphe nucleus (DRN). In vitro experiments have demonstrated that nicotine increases the firing activity in the majority of DRN 5-HT neurons and that DRN contains nicotinic acetylcholine receptors (nAChRs) located at both somata and presynaptic elements. One of the most common presynaptic effects of nicotine is to increase glutamate release. Although DRN receives profuse glutamatergic afferents, the effect of nicotine on glutamate release in the DRN has not been studied in detail. Using whole-cell recording techniques, we investigated the effects of nicotine on the glutamatergic input to 5-HT DRN neurons in rat midbrain slices. Low nicotine concentrations, in the presence of bicuculline and tetrodotoxin (TTX), increased the frequency but did not change the amplitude of glutamate-induced EPSCs, recorded from identified 5-HT neurons. Nicotine-induced increase of glutamatergic EPSC frequency persisted 10-20 min after drug withdrawal. This nicotinic effect was mimicked by exogenous administration of acetylcholine (ACh) or inhibition of ACh metabolism. In addition, the nicotine-induced increase in EPSC frequency was abolished by blockade of α4β2 nAChRs, voltage-gated calcium channels, or intracellular calcium signaling but not by α7 nAChR antagonists. These data suggest that both nicotine and endogenous ACh can increase glutamate release through activation of presynaptic α4β2 but not α7 nAChRs in the DRN. The effect involves long-term changes in synaptic function, and it is dependent on voltage-gated calcium channels and presynaptic calcium stores.